Fuzzy Stability of a Quadratic-Additive Functional Equation - Sun Sook Jin; Yang Hi Lee (International Journal of Mathematics and Mathematical Sciences)
We investigate a fuzzy version of stability for the functional equation 𝑓(𝑥+𝑦+𝑧+𝑤)+2𝑓(𝑥)+2𝑓(𝑦)+2𝑓(𝑧)+2𝑓(𝑤)−𝑓(𝑥+𝑦)−𝑓(𝑥+𝑧)−𝑓(𝑥+𝑤)−𝑓(𝑦+𝑧)−𝑓(𝑦+𝑤)−𝑓(𝑧+𝑤)=0.